Restricted cell cycle is essential for clonal evolution and therapeutic resistance of pre-leukemic stem cells - Cedric S. Tremblay (Nature Portfolio, 2018)
Cell cycle kinetics of pre-leukemic stem cells (pre-LSCs) may be an important determinant of clonal evolution and therapeutic resistance. Here, the AUs use a transgenic T-ALL mouse model that allows non-dividing cells to be tracked and identify a subset of non-dividing pre-LSCs maintained by p21.